Benchmarking the ability of novel compounds to inhibit SARS-CoV-2 main protease using steered molecular dynamics simulations. (July 2022) - Singh, Rahul; Bhardwaj, Vijay Kumar; Das, Pralay; Bhattacherjee, Dhananjay; Zyryanov, Grigory V.; Purohit, Rituraj
Abstract: Background: The SARS-CoV-2 main protease (M pro ) is an attractive target in the COVID-19 drug development process. It catalyzes the polyprotein's translation from viral RNA and specifies a particular cleavage site. Due to the absence of identical cleavage specificity in human cell proteases, targeting M pro with chemical compounds can obstruct the replication of the virus. Methods: To explore the potential binding mechanisms of 1, 2, 3-triazole scaffolds in comparison to co-crystallized inhibitors 11a and 11b towards M pro, we herein utilized molecular dynamics and enhanced sampling simulation studies. Results and conclusion: All the 1, 2, 3-triazole scaffolds interacted with catalytic residues (Cys145 and His41) and binding pocket residues of M pro involving Met165, Glu166, Ser144, Gln189, His163, and Met49. Furthermore, the adequate binding free energy and potential mean force of the topmost compound 3h was comparable to the experimental inhibitors 11a and 11b of M pro . Overall, the current analysis could be beneficial in developing the SARS-CoV-2 M pro potential inhibitors. Graphical abstract: Image 1 Highlights: Molecule 3h interacted with catalytic dyad residues Cys145 and His41 of SARS-CoV-2 main protease. Molecule 3h represent a promising therapeutic lead for the treatment of COVID-19. Molecule 3h could be developed as SARS-CoV-2 main protease inhibitor. The PMF profile of 3h suggested a comparable affinity to the standard molecules.